O ensino primário nos espaços-tempos da I República no Brasil (1889-1930) e em Portugal (1910-1926) - Fernandes, Ana Lúcia; Correia, Luís Grosso (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This article is the fi rst result of an ongoing comparative study of the education systems in the spaces-times of the earliest republican regimes established in Brazil (1889-1930) and Portugal (1910-1926). It takes as reference the reforms introduced in primary education, curriculum and teacher training processes of both countries and outlines a conclusion/comparison, having as historical backdrop the educational solutions taken in France in the 1880s (with the principle of secularism on the top).